Polyphenolic profile of persimmon leaves by high resolution mass spectrometry (LC-ESI-LTQ-Orbitrap-MS). (May 2016) - Heras, Ruth Martínez-Las; Quifer-Rada, Paola; Andrés, Ana; Lamuela-Raventós, Rosa
Highlights: The phenolic profile of persimmon ( Diospyros kaki L.) leaves has been analysed by high resolution mass spectrometry. Forty-one phenolic compounds were identified using high mass accuracy and confirmed by MS 2 experiments. Thirty-three polyphenols are reported in persimmon leaves for the first time. Abstract: Persimmon leaves have played an important role in Chinese medicine. Persimmon extracts and formulations have been shown to possess a wide range of pharmacological activities, including antioxidant, hypolipidaemic and antidiabetic, and they have been used to treat cardiovascular disease, improve homeostasis, as antibacterial and anti-inflammatory agents, and as a beauty treatment. In this work, liquid chromatography coupled to hybrid linear ion trap quadrupole Orbitrap mass spectrometry was used to accurately identify persimmon leaf polyphenols. Forty-one phenolic compounds, including simple phenolic acids, hydroxybenzoic acids, hydroxycinnamic acids, flavanols, flavonols, flavanones, flavone-chalcones, tyrosols and their conjugated derivatives, were identified and quantified using high mass accuracy data and confirmed by MS 2 experiments. To the best of our knowledge, this is the most extensive study of persimmon leaf polyphenols performed so far, since 33 phenolic compounds are reported for the first time.